Harnessing Emotional Connections to Improve Financial Decisions Evaluating the Impact of Financial Education in Mainstream Media - Berg, Gunhild (The World Bank, 2013)
This paper exploits the emotional connections and viewer attentiveness of mainstream media to evaluate the economic impact of financial education messages on debt management delivered through a popular television soap opera in South Africa. The study uses a symmetric encouragement design to compare outcomes of individuals who were randomly assigned to watch a soap opera with financial messages, "Scandal!" to those of individuals who were invited to watch a similar soap opera without financial messages, "Muvhango." Both shows overlapped in evening primetime and had similar past viewership profiles. The financial storyline spanned two months and featured one of the leading characters of the show borrowing excessively and irresponsibly through hire-purchase, gambling, and ending up in financial distress; and eventually seeking help to find her way out. Two intermediate and one final follow-up surveys were conducted as part of the study. The analysis finds individuals assigned to watch Scandal had significantly higher financial knowledge of the issues highlighted in the soap opera storyline, in particular messages delivered by the leading character. On behavior, Scandal viewers were almost twice more likely to borrow from formal sources, less likely to engage in gambling, and less prone to enter hire purchase agreements. Messages promoting a national debt mediation helpline delivered by an external character did not sustain traction beyond immediate interest. Three qualitative focus groups highlight the importance of emotional connections with the leading character in motivating behavior change